Toward estimating the impact of changes in immigrants' insurance eligibility on hospital expenditures for uncompensated care - Curtis Lesley H; Sendersky Veronica; Timbie Justin W; Castel Liana D; Feather Keith A; Schulman Kevin A (BMC, 2003)
Abstract Background The Personal Responsibility and Work Opportunity Reconciliation Act (PRWORA) of 1996 gave states the option to withdraw Medicaid coverage of nonemergency care from most legal immigrants. Our goal was to assess the effect of PRWORA on hospital uncompensated care in the United States. Methods We collected the following state-level data for the period from 1994 through 1999: foreign-born, noncitizen population and health uninsurance rates (US Census Current Population Survey); percentage of teaching hospitals (American Hospital Association Annual Survey of Hospitals); and each state's decision whether to implement the PRWORA Medicaid bar for legal permanent residents or to continue offering nonemergency Medicaid coverage using state-only funds (Urban Institute). We modeled uncompensated care expenditures by state (also from the Annual Survey of Hospitals) in both univariate and multivariable regression analyses. Results When measured at the state level, there was no significant relationship between uncompensated care expenditures and states' percentage of noncitizen immigrants. Uninsurance rates were the only significant factor in predicting uncompensated hospital care expenditures by state. Conclusions Reducing the number of uninsured patients would most surely reduce hospital expenditures for uncompensated care. However, data limitations hampered our efforts to obtain a monetary estimate of hospitals' financial losses due specifically to the immigrant eligibility changes in PRWORA. Quantifying the impact of these provisions on hospitals will require better data sources.